Tantangan dalam Mengungkap Beban Kerja Mental - Ni Made Swasti Wulanyani (Faculty of Psychology Universitas Gadjah Mada, 2013)
The concept of mental workload leads to attentional demands experienced during cognitive tasks. The concept is more challenging than the physical workload. The physical workload can be observed, predictable and more easily measured objectively, but it is not the case with mental workload. Workload analysis is useful in providing information about the demands of the task in accordance with the limitations of workers and to optimize its system. Mental workload arising from the interaction between the operator and the task environment. Therefore, individual differences can not be ignored. Some researchers claim that subjective measurement method is quite effective, but other researchers assume that the subjective method is less precise because the workload is not measured when a person is doing his job. Objective methods are not easy to usebecause it requires specialized equipment and must be performed by a trained person.